How does a Digital Government impact Energy Transition in Gulf economies? - Bousrih, Jihen (Journal of Ecohumanism, 2024)
In the global economy, the oil and gas sector has been crucial. It supplies the energy needed for global production, transportation, and heating systems. Natural gas and crude oil have been essential for advancing economic development. However, there are financial and environmental costs associated with our reliance on fossil fuels. The transition towards a sustainable environment with low-carbon energy makes clean energy solutions more and more popular among businesses, consumers, and nations. It reduces dependence on gas and oil and diversifies energy portfolios. This paper applies a panel approach to Gulf Cooperation Council countries from 2005 to 2022 to investigate the effect of digitalizing government on the energy transition process in the Middle East. On the one hand, the results show that online services, human development, and infrastructure have a positive and significant impact on renewable energies for the GCC countries. On the other hand, the findings focus on the importance of a digital government in resource management.